Congenital birthmarks: A common finding in newborns - Martins,Cátia (2024)
Abstract Epidermal nevi are generally benign, isolated conditions, occurring in approximately 1 to 3 per 1,000 newborns, with sebaceous nevi accounting for approximately half of cases. The authors present two clinical cases of newborns with different subtypes of congenital epidermal nevi: a papillomatous epidermal nevus and a sebaceous nevus. Epidermal nevi typically present as a single benign lesion. However, in some cases  especially when the lesions are large or extensive  they may be associated with syndromic forms involving other organs, most commonly the brain, eye, and skeletal systems. Early recognition of these skin lesions at birth is crucial, as it allows fot appropriate clinical management and early detection of any extracutaneous abnormalities.